EVALUATING THE EFFICACY OF DISCORD-BASED BLENDED LEARNING ON ENGLISH SPEAKING SKILLS AND STUDENT ENGAGEMENT - Munibi, Ahmad Zaki; Boeriswati, Endry; Anoegrajekti, Novi; Rahmat, Aceng (JURNAL EDUSCIENCE, 2024)
In the midst of the growing prominence of educational technology, Discord emerges as a promising platform for facilitating language learning. Nevertheless, its role in blended learning models aimed at improving English speaking skills and student engagement, particularly among middle school students, remains insufficiently examined. This study explores the application of Discord, a social communication tool, within a blended learning framework to enhance English speaking skills among middle school learners. Using a qualitative case study method, the research involves 23 purposively sampled students representing diverse levels of English proficiency. Data is gathered through classroom observations, teacher interviews, and document analysis. The literature underscores the critical role of fluent speaking skills in language education, highlighting various influencing factors, such as speaking conditions, attitudes, listening skills, and feedback. Discord's distinctive features such as voice channels and instant messaging facilitate real-time communication and collaborative learning opportunities. While prior studies have predominantly concentrated on traditional educational technologies, they often overlook the potential of emerging platforms like Discord. The findings indicate that Discord significantly enhances interactivity, collaboration, and multimedia integration in learning activities. Educators utilize Discord's functionalities to host engaging discussions, deliver diverse learning materials, and conduct both formative and summative assessments effectively. Students report enhanced collaboration, active participation, and improved language proficiency through the platform's use. Integrating Discord into a blended learning approach offers an innovative and effective solution for language education, addressing the shortcomings of conventional methods and fostering a more engaging learning atmosphere. This research contributes valuable empirical insights into Discord's effectiveness in improving English speaking skills and promoting student engagement, while providing actionable recommendations for educators aiming to integrate advanced technologies into language teaching.Keywords: Discord; Blended Learning; English Speaking Skills; Student Engagement